Measuring the cosmic bulk flow with 6dFGSv. Issue Volume 11:Issue S308(2015) (12th October 2016) - Magoulas, Christina; Springob, Christopher; Colless, Matthew; Mould, Jeremy; Lucey, John; Erdoğdu, Pirin; Jones, D. Heath
Abstract: While recent years have seen rapid growth in the number of galaxy peculiar velocity measurements, disagreements remain about the extent to which the peculiar velocity field - a tracer of the large-scale distribution of mass - agrees with both ΛCDM expectations and with velocity field models derived from redshift surveys. The 6dF Galaxy Survey includes peculiar velocities for nearly 9 000 early-type galaxies (6dFGSv), making it the largest and most homogeneous galaxy peculiar velocity sample to date. We have used the 6dFGS velocity field to determine the amplitude and scale of large-scale cosmic flows in the local universe and test standard cosmological models. We also compare the galaxy density and peculiar velocity fields to establish the distribution of dark and luminous matter and better constrain key cosmological parameters such as the redshift-space distortion parameter.